A food synergy approach in a national program to improve the micronutrient status of preschoolers: a randomized control trial protocol. Issue 1 (21st August 2018) - Roychoudhury, Dripta; Nair, Krishnapillai Madhavan; Balakrishna, Nagalla; Radhakrishna, Kankipati Vijaya; Ghosh, Sudip; Fernandez Rao, Sylvia
Abstract: Iron deficiency anemia (IDA) is a significant public health issue in India affecting nearly all vulnerable segments of the population. Causes of IDA include low consumption of iron‐rich foods combined with poor iron bioavailability of nonheme iron sources. To date, interventions aimed at correcting IDA focus on increasing iron intake through iron supplementation or fortification strategies. In contrast, dietary diversification is a long‐term sustainable approach to improve bioavailable iron intake. In this context, the inclusion of vitamin C–rich fruits in the regular diet has proven to improve iron absorption, but the effect on iron status is inconclusive. Considering the ongoing national program for preschoolers in India, we designed a cluster randomized controlled trial (RCT) to test the hypothesis that inclusion of vitamin C–rich fruit in a regular meal would improve iron absorption and lead to better child iron and micronutrient status, cognitive development, gut health, and growth while reducing morbidity. This paper illustrates a context‐specific framework and activities to design and functionalize an open‐label, three‐arm cluster RCT to test a specific hypothesis. The results of this designed trial should generate evidence to inform policy on the effect of a food‐based intervention on iron status. Abstract : To combat iron deficiency anemia, a long‐term sustainable approach would be dietary diversification to improve bioavailable iron intake. Inclusion of vitamin C–rich fruits in the regular diet has proven to improve iron absorption. This paper describes the design of a randomized controlled trial in India to test the hypothesis that inclusion of vitamin C–rich fruit in a regular meal would improve iron absorption and lead to better child iron and micronutrient status.